Cidofovir‐induced anterior uveitis in an allogeneic stem cell transplant recipient. Issue 6 (28th October 2022) - O'Brien, Aine; Boan, Peter
Abstract: Anterior uveitis is a reported complication of intravenous cidofovir, almost exclusively described in human immunodeficiency virus (HIV) infected patients treated for cytomegalovirus retinitis. In this study, we report the case of an allogeneic stem cell transplant recipient with significant visual impairment and hypotony following administration of high‐dose intravenous cidofovir for hemorrhagic cystitis due to BK virus.